คุณค่าทางโภชนะของกากนมถั่วเหลืองหมักโดย Aspergillus niger เพื่อใช้เป็นอาหารสัตว์ - พิมพา นวิญญา; ศรีชนะ ดรุณี (Thai Journal of Science and Technology, 2020)
Soymilk residue is a by-product from soymilk production and dried soymilk residue is a source of protein, energy and fiber. Improving its nutritional value would make it more suitable for use as feed stuff. Therefore, the objective of this study was to investigate the nutritional value and dry matter digestibility in rumen in vitro of fermented soymilk residue by Aspergillus niger TISTR3013 (FSR) for 3, 5 and 7 days. The results showed that crude protein was most increased (33.48 %DM) whereas dry matter, organic matter, NDF, ADF and gross energy were decreased for 7-day FSR when compared to those of 3-day FSR and 5-day FSR. Furthermore, dry matter digestibility in rumen was highest (81.08 %) for 7-day FSR and lowest for the non-fermented soymilk residue (56.23 %). The results from these experiments showed that fermentation of soymilk residue with A. niger TISTR3013 increased protein, decreased NDF, ADF and increased dry matter digestibility in rumen.